Continuous Monitoring of Wound Healing Using a Wearable Enzymatic Uric Acid Biosensor. Issue 8 (16th May 2018) - RoyChoudhury, Sohini; Umasankar, Yogeswaran; Jaller, Jose; Herskovitz, Ingrid; Mervis, Joshua; Darwin, Evan; Hirt, Penelope A.; Borda, Luis J.; Lev-Tov, Hadar A.; Kirsner, Robert; Bhansali, Shekhar
Abstract : Wound management involves repeated clinical trips and procedures of lab tests over days. To eliminate this time lag and provide real-time monitoring of a wound's progress, we have designed an enzymatic biosensor for determining uric acid (UA) in wound fluid. Uric Acid is a biomarker, having an established correlation with wounds and their healing. This electrochemical biosensor comprises enzyme urate oxidase (uricase, UOx) entrapped in a polyvinyl alcohol based cationic polymer for enhanced stability. Results show that the use of a redox electron shuttle, ferrocene carboxylic acid (FCA), enabled electron transfer between the enzyme and the transducer. The immobilized uricase in the polymer matrix provided stable continuous measurements at body temperature for a week with minimal deviation. Detection of uric acid in wound fluid has been determined from volumes as low as 0.5–50μL. Studies from different wound samples have shown an average recovery of 107%. The sensor has been interfaced with LMP91000 potentiostat and controlled by CC2650 microcontroller on a Kapton tape-based miniaturized flexible platform.